Phylogenetic variability of Human Metapneumovirus in patients with acute respiratory infections in Cameroon, 2011–2014 - Sebastien Kenmoe (Journal of Infection and Public Health, 2020)
Background: Identified in 2001, Human Metapneumovirus (HMPV) is a Pneumovirus associated with acute lower and upper respiratory infections in all age groups and especially in newborns, elderly and immunocompromised subjects. Data are still limited in sub-Saharan African countries genetic characterization of this respiratory virus. This study reports the genetic variability of HMPV strains in Cameroonian children for 3 consecutive epidemic seasons (September 2011–October 2014). Methods: A prospective surveillance was conducted to identify inpatient and outpatient children less than 15 years with respiratory symptoms ≤5 days. The nasopharyngeal samples were tested for HMPV using a multiplex polymerase chain reaction. Viral distribution and demographic data were analyzed statistically. Positive samples for HMPV were amplified by semi-nested polymerize chain reaction and then partially sequenced at the G gene. Phylogenetic analyzes were performed on the partial nucleotide and protein sequences of the G gene. Results: From September 2011 to October 2014, 822 children under 15 years were enrolled in the study. HMPV was identified in each of 3.9% (32/822) of children. HMPV were detected throughout the year. HMPV-A (73.3%; 11/15) was predominant compared to HMPV-B (26.7; 4/15). Cameroonian HMPV strains are grouped among the members of genotype A2b (for HMPV-A), B1 and B2 (for HMPV-B). Conclusion: This study suggests that about 4% of ARI recorded in children in Cameroon are caused by HMPV. The present study is also the first report on the genetic variability of the G gene of HMPV strains in the region. Although this work partially fills gaps for some information, additional studies are required to clarify the molecular epidemiology and evolutionary pattern of HMPV in sub-Saharan Africa in general and more particularly in Cameroon. Keywords: Acute respiratory infections, Human Metapneumovirus, Genetic variability, Sub-Saharan Africa, Cameroon